Effect of non-surgical periodontal therapy on clinical and immunological response and glycaemic control in type 2 diabetic patients with moderate periodontitis - Ana Bele´n Navarro-Sanchez (Blackwell Synergy, 2007)
Objetives: The purpose of this study was to compare the local efficacy of nonsurgical periodontal therapy between type 2 diabetic and non-diabetic patients and the effect of periodontal therapy on glycaemic control. Background: A complex two-way relationship exists between diabetes mellitus and periodontitis. Material and Methods: After selection, 20 subjects (10 diabetic and 10 non-diabetic) underwent baseline examination, periodontal clinical study and biochemical analysis of gingival crevicular fluid (GCF). After the pre-treatment phase, subgingival scaling and root planing were performed. Subsequently, all subjects continued the maintenance programme and were re-examined at 3 and 6 months. Results: Diabetic and non-diabetic subjects responded well after therapy, showing a very similar progression during the follow-up period. Both groups showed clinically and immunologically significant improvements. Significant reductions were also found in the total volume of GCF and levels of interleukin-1b and tumour necrosis factor-a.Diabetic subjects showed an improvement in theirmetabolic control. The change in glycosylated haemoglobin (HbA1C) was statistically significant at 3 and 6 months. Conclusions: The clinical and immunological improvements obtained were accompanied by a significant reduction in HbA1C values in type 2 diabetic subjects. Larger studies are needed to confirm this finding and establish whether periodontal therapy has a significant effect on glycaemic control.